Pengembangan Media Video Slideshow Berbasis Android Materi Siklus Daur Air - Rukmoko, Arif (CV. Creative Tugu Pena, 2022)
This study aims to develop innovative learning media that is in line with the changing times, effective and practical makes it easier for teachers to convey learning about the material of the water cycle in the classroom more varied. This study uses a type of Research and Development (R&D), a strategy or research method to improve practice. The subjects of the media use test were teachers and fifth grade MI students in Bulu region, Temanggung Regency. Android-based slideshow media is used as learning media. The development of instructional media with a slideshow on learning and understanding of science material is done by (a) conducting preliminary research, (b) carrying out planning (defining abilities, formulating objectives, determining material and sequence of learning, (c) developing learning media with slideshows, (d) ) Material expert test and media expert test, (e) Small-scale initial and revised field test, (f) Large-scale and final revision test, (g) application in learning. The result of the research of the development of water cycle material media through an Android-based video slideshow in MI in Bulu sub-district of Temanggung Regency based on the results of the calculation of the independent sample t-test revealed an average increase in the experimental group of 2.79 while an increase in control class by 0.81 so that an increase in the score learning experimental class 1.98 greater than the control class. It is also known that the t account of 8.270 with a significance of 0.000. The t-table value of db 63 is 1,998. So it can be concluded that t aaccount> t table (8.270> 1.998) and the significance value is less than 0.05 (p = 0.000 <0.05), so it can be stated that there are significant differences in the increase in learning outcomes significantly in the experimental group and control group. Keywords: Developing Learning Media, Learning Based Android, Developing Media Video